2017
DOI: 10.1016/j.ijhydene.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Combined micro-cogeneration and electric vehicle system for household application: An energy and economic analysis in a Northern European climate

Abstract: In recent years, Denmark boosted investments in renewable energy and electrification of transportation. The Danish Agenda proposed that all primary energy consumption will be covered by renewable sources such as wind, biomass and solar by 2050. These changes require significant investment and re-thinking of entire energy infrastructures and types of consumption. The Agenda also suggested, among other things, improving the efficiency of energy systems. \ud \ud In this paper, the interactions between charging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…Moreover, reported data on the average DHW heat consumption are of the same order of magnitude of the electric need of the house [54], indicating that a refinement of the accumulation system is a realistic alternative to higher fuel inputs.…”
Section: -Sanitary Water Yieldmentioning
confidence: 94%
“…Moreover, reported data on the average DHW heat consumption are of the same order of magnitude of the electric need of the house [54], indicating that a refinement of the accumulation system is a realistic alternative to higher fuel inputs.…”
Section: -Sanitary Water Yieldmentioning
confidence: 94%
“…For example, the energy-saving effect of a combined use of a residential SOFC cogeneration system that adopted a continuous operation, and a plug-in hybrid electric vehicle was discussed by optimal operational planning based on mixed-integer linear programming [19]. Also the authors of the present paper previously investigated the interactions between charging an electric car and a micro-SOFC with an integrated heating system cogeneration system for a household application [20]. In another study [21], the authors analyzed a SOFC, heat pump and Stirling engine system to face heating, domestic hot water and electricity demands for a residential user.…”
Section: 1literature Review On Sofc Small Cogeneration Systemsmentioning
confidence: 99%
“…Electric power is commonly provided from the national grid while heating or hot water is generated from a fuel driven boiler. Several studies found that the fuel cell-based cogeneration system is more promising to reduce primary energy consumption, energy cost and carbon emission generated by the system compared to the CSS [55,57,58].…”
Section: Evaluation Of the System Designmentioning
confidence: 99%